COVID-19 pandemic: what factors compromised the mental capacity to work of nursing technicians? - Katia Maria Rosa Vieira; Francisco Ubaldo Vieira Junior; Zélia Zilda Lourenço de Camargo Bittencourt (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify the factors that influenced the mental capacity to work of nursing technicians during the COVID-19 pandemic. Methods: a cross-sectional study, carried out at two reference hospitals in assisting the population during the COVID-19 pandemic. A total of 237 professionals from Intensive Care Units participated and answered a questionnaire. Multiple linear regression models were used to assess the correlation between mental capacity to work and variables related to risks of contamination, institutional support and health. Results: lack of COVID-19 tests, lack of knowledge of routine, absences in 2021 and mental illness contributed to worse mental capacity to work. Management embracement and physical capacity were considered protective factors. Conclusions: reduced work capacity in relation to mental demands can affect professional performance and quality of care, with implications for patients and health institutions.